ANALISIS STRATEGI PMBELAJARAN INSTRUMN DRUM KELAS JUNIOR DI YAMAHA MUSIC SCHOOL PONTIANAK - Vega Damryanan; Ismunanar Ismunanar; Chrisstianli Silaban (Universitas Tanjungpura, 2019)
AbstractThe purpose of doing this thesis is to know the studying strategy in drum class in Pontianak Junior Yamaha Music School where found junior class that the students are under 15 years old. Therefore, in teaching them how to play drum in a proper way, technic and special way is needed and one of it is studying strategy. Yamaha music school also has international standard that makes the writer wanted to know the strategy of teaching drum in junior class. The method used in this research is descriptive method in form of qualitative research. From the interview result, the writer know that the teaching strategy in junior class Yamaha Music School are expository teaching strategy which means teaching or explaining and inquiry means practicing or exercising. Those are the reasons why the writer recommending to use expository and inquiry strategy are applied in teaching in school. Keywords: Snare Drum, Extracurricular